Periodic global One Health threats update - Reperant, L.; Mackenzie, John; Osterhaus, A. (2016)
Emerging infectious diseases continue to impose unpredictable burdens on global health and economy. Infectious disease surveillance and pandemic preparedness are essential to mitigate the impact of future threats. Global surveillance networks provide unprecedented monitoring data on plant, animal and human infectious diseases. Using such sources, we report on current major One Health threats and update on their epidemiological status.